2012
DOI: 10.1111/cid.12006
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Randomized Study on the Immediate Loading of Mandibular Overdentures Supported by One or Two Implants; A 3 Year Follow‐Up Report

Abstract: No significant differences were found between subjects in the two groups with respect to implant survival and peri implant bone loss, and patient satisfaction scores continued to be high for both groups. Need for denture maintenance was low in both groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
193
1
3

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(206 citation statements)
references
References 14 publications
9
193
1
3
Order By: Relevance
“…This technique could potentially provide immediate function and esthetics to the patient. 44 However, it is yet unknown how predictable this approach is. A 3-to 8-year prospective study 45 has been conducted on 328 implants placed in the anterior region of the mandible and were immediately loaded with implant-retained overdentures.…”
Section: Discussionmentioning
confidence: 99%
“…This technique could potentially provide immediate function and esthetics to the patient. 44 However, it is yet unknown how predictable this approach is. A 3-to 8-year prospective study 45 has been conducted on 328 implants placed in the anterior region of the mandible and were immediately loaded with implant-retained overdentures.…”
Section: Discussionmentioning
confidence: 99%
“…The selected nine studies 6,[27][28][29][30][31][32][33][34] were RCTs and were published between 1998 to 2016. The observation period ranged from 12 months to 10 years.…”
Section: Characteristics Of Included Studies:-mentioning
confidence: 99%
“…All of the studies were conducted in a university setting; four trials were conducted in Netherlands [27][28][29][30] , two studies in Canada 33,34 two studies in Egypt 31,32 and one in Germany 6 . Six studies reported delayed loading protocol [27][28][29][30][31][32] while the other three studies 6,33,34 followed an early/immediate loading protocol. In early loading protocol, the dentures were inserted 42 days after implant placement 33 whereas in immediate loading protocol the denture were inserted at time of surgical implant placement 1329 34 .…”
Section: Characteristics Of Included Studies:-mentioning
confidence: 99%
See 1 more Smart Citation
“…15] consensus that the use of 2 implants is recommended to ensure a successful rehabilitation of the mandibular edentulous patient. However, other authors [16,17] have concluded that even a single implant might be used to achieve a good stability of the overdenture. Ball attachments are able to prevent horizontal movement of the denture on the mucosa, but it is not possible to prevent the vertical axial movement of the balls in the matrix.…”
Section: Ball Attachmentsmentioning
confidence: 99%